2015
DOI: 10.1182/blood.v126.23.4536.4536
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood Hemogram: What Is the Effect of Maternal Anemia?

Abstract: Introduction: Umbilical cord blood (UCB), a source of hematopoietic stem cells, represents neonatal blood and reflects the health of the newborn to a great extent. Establishing biological reference intervals is essential to discard samples before submitting for expensive investigations and storage. Also neonatal anemia has to be recognised early. Hence this study is undertaken to establish a biological reference interval for the UCB hemogram and to study the effect of maternal anemia on the fetus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some studies confirm that cord blood haemoglobin and newborn weight showed a significant variation due to maternal anaemia [ 6 ], even though it has been reported that routine haematological values of newborns have no dependency on the maternal haematological values [ 7 ]. Maternal habits like smoking or alcohol consumption, medical problems like diabetes mellitus, eclampsia, hypertension [ 8 ] and also the mode of delivery, frequency of pregnancy, obstetrics and abortion history affect the haematological profile of neonates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies confirm that cord blood haemoglobin and newborn weight showed a significant variation due to maternal anaemia [ 6 ], even though it has been reported that routine haematological values of newborns have no dependency on the maternal haematological values [ 7 ]. Maternal habits like smoking or alcohol consumption, medical problems like diabetes mellitus, eclampsia, hypertension [ 8 ] and also the mode of delivery, frequency of pregnancy, obstetrics and abortion history affect the haematological profile of neonates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 The umbilical cord blood Hb is an essential predictor of anemia in newborns at delivery. 8 It was formerly assumed that regardless of the mother's Hb level, the baby would not be anemic. According to several research, women who had iron deficiency anemia during pregnancy gave birth to babies with decreased Hb levels in their cord blood.…”
Section: Introductionmentioning
confidence: 99%